The Effectiveness of the use of information and communication technology (ICT) in diaspora engagement for the purpose of national development - SENIOR, Lasheree Syrica (KDI School, 2016)
Migration as a result of increased globalization has impacted population distribution worldwide and many countries now have considerably large Diasporas. These groups represent a valuable resource for exploitation by and partnership with governments for the purpose of social and economic development in their respective mother countries or homeland. In the face of advancements in Information and Communication Technology (ICT) and the changing composition of the Diaspora’s constituents, the need for governments to procure effective tools and develop technologically innovative ways to engage Diaspora members who are increasingly technologically savvy, has become increasingly important. Using primary data collected from individual Jamaican Diaspora members and representatives of key Government stakeholders in the Diaspora engagement process, as well as secondary data from previous research in the form of journal articles and case studies, this qualitative paper : (1) measures the perceived level of ineffectiveness of the current ICT-based Diaspora engagement mechanism in enhancing Jamaican national development, (2) identifies the major issues; and (3) recommends best practices for extrapolation in Jamaica. In order to capture the impact of Diaspora engagement on national development In order to capture the impact of Diaspora engagement on national development, an attempt was made to find a correlation between effective engagement, particularly second and subsequent generation members and their willingness to contribute to national development processes in the homeland, Jamaica. This paper also provides evidence that failure to adapt to advances in information and communication technology affects Diaspora engagement effectiveness and weakens cultural affinity and patriotism. These findings support the idea that government’s increased investment in more modern information and communication technology tools, particularly in line Ministries, Departments and Agencies (MDAs) which liaise directly with Diaspora members, is necessary, as it has the capacity to improve the efficacy of current engagement levels, and, by extension, increase the contributions of this group to social and economic national development, particularly those members who are from second and subsequent generations, as they are more likely to be less patriotic and increasingly lacking in cultural affinity to the homeland.
Thesis(Master) --KDI School:Master of Development Policy,2016